'We're Giving Them Choice Which Is Controlled Choice'—Care Managers' Views on Finding Social Care Support for People with Learning Disabilities. (20th September 2019) - Richardson, Lisa; Turnpenny, Agnes; Whelton, Beckie; Beadle-Brown, Julie
Abstract: Choice and control are pivotal in UK Government policy for achieving personalisation of social care for people with learning disabilities; however, little is known about the role care management plays in supporting people with learning disabilities finding social care services. This article explores that the support care managers provide people with learning disabilities, how care managers source and use information to offer choice in relation to accommodation and support, with a focus on people receiving managed budgets. Qualitative interviews with eight care managers from two local authorities in the South East of England were analysed using thematic network analysis, producing three global themes. The first 'shaping choice' describes the role of the care management process and assessments have in determining opportunities for choice. The gathering and interpretation of quality information is explored in the second global theme, highlighting the role of visiting settings to understand their quality. 'Choice in principle' is the third global theme, whereby the factors shaping choice come to be seen as choice akin to that anyone else has. These findings have implications for future policy and practice in relation to care management for people with learning disabilities.